Cornulitids (tubeworms) from the Late Ordovician Hirnantia fauna of Morocco - Gutiérrez-Marco, J. C.; Vinn, Olev (Journal of African Earth Sciences, 2018)
Two species of cornulitids, Cornulites gondwanensis sp. nov. and C. aff. shallochensis Reed are described from the Hirnantian of Morocco, within an assemblage representative of the Hirnantia brachiopod fauna occurring near the Ordovician South Pole. The dominance of aggregated and solitary free forms could be explained by particular sedimentary environments preceding the Hirnantian glaciation and the latest Ordovician Extinction Event. The diversity of cornulitids in the Late Ordovician of Gondwana and related terranes was relatively low, and less diverse than the cornulitids of Laurentia and Baltica. Hirnantian cornulitids from Morocco do not resemble Late Ordovician cornulitids of Baltica and Laurentia. Moroccan cornulitids seem to be closely allied to some older Gondwanan cornulitids, especially Sardinian ones. They resemble species described from the Late Ordovician and Llandovery of Scotland suggesting a palaeobiogeographic link. Financial support to O.V. was provided by an Estonian Research Council projectIUT20-34 ‘The Phanerozoic journey of Baltica: sedimentary, geochemical and biotic signatures of changing environment – PalaeoBaltica’. Field-work in Morocco (J.C.G.-M.) has been supported by the IBEROR project (ref. CGL2012-39471/BTE) of the Spanish Ministry of Economy, Industry and Competitiveness. Peer reviewed